(untitled) (Hekima Review, 2014)
Migration is not a new phenomenon in human history inasmuch as the earth was populated thanks to human mobility. Nevertheless, “today’s migration makes up the vastest movement of people of all times,” certainly because of our globalized world, which offers facilities to travel and communicate. In this “vast movement of people,” some people move by choice, while others are forced to leavetheir home place by external causes (like natural disasters, political instability, civil wars, economic problems). That is why “in these last decades, the phenomenon… has turned into a structural reality of contemporary society. It is becoming an increasingly complexproblem from the social, cultural, political, religious, economic and pastoral points of view” (Ibid.). And for the Catholic Church, migration is a “sign of the times:” When talking about migration, one can distinguish three groups: legal, forced and undocumented migrants. The first category comprises persons who enter another country with legal documents; the second is made of people (e.g. refugees) who cross the borders of another country due to external causes (like war or natural disaster), and the third group, the undocumented migrants, decide to leave their home places without proper documents, looking for jobs abroad. Now, “because paths to legal immigration are limited, despite the economic and demographic need, migrants seeking work often must proceed without official travel authorization.”